Increasing of N-uptake by Inoculation of Diazotroph Endophytic Bacteria in Vermiculite Media - DWI N. SUSILOWATI; RATIH SARASWATI; R.D HASTUTI; E. YUNIARTI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2007)
Intensive selection of selected 15 isolates on N2-fixing activities and auxin production to diazotroph endophytic bacteria showed that five isolates were superior, that is KACP12 (0.2569 μmol hour-1 culture-1), KACP13 (0.3026 μmol hour-1 culture-1), KACP21 (0.4592 μmol hour-1 culture-1), KACP32 (0.3131 μmol hour-1 culture-1), and KAMG2 (0.4843 μmol hour-1 culture-1). Inoculated five superior isolates into soybean seeds in vermiculite media showed that soybean plant inoculated by KAMG2 has the highest nitrogenase specific activity compared to others and control, that is 2,54 ± 1,2 μmol hour-1 plant-1. However inoculation with KACM and KACP32 showed higher N-uptake of soybean plant. Although this research has conducted within theearly stage of soybean plant growth, it is obvious that inoculated diazotroph endophytic bacteria in vermiculite media seem to be a good method to introduce selected strain envisaging growth promoting and nitrogen fixation.